Conservation Laws and Exact Solutions to the Modified Hyperbolic Geometric Flow (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate Lie symmetry group, optimal system,exact solutions and conservation laws of modified hyperbolic geometric flowvia Lie symmetry method. Then, conservation laws of modified hyperbolicgeometric flow are obtained by applying Ibragimov method.
Keywords: The modified hyperbolic geometric flow; exact solution; conservation law.